Balancing fidelity, acceptability, and readability in children’s story translation - Herianto, Herianto; Khrisna, Dyah Ayu Nila; Dewi, Ida Kusuma; Budiharjo, Bayu; Kusumastuti, Fenty; Nababan, Mangatur (Universitas Dian Nuswantoro, 2025)
Children’s literature is crucial for the cognitive, emotional, and social development of young readers. In line with the Agency for Language Development and Cultivation’s initiatives to translate children’s books, this study aims to identify which aspects of translation quality are most effectively maintained and how they impact target readers, particularly regarding engagement across various reading levels. This descriptive qualitative study employed a product-oriented approach with a multiple-case study design to evaluate different reading levels on the Penjaring website. A purposive sampling technique was utilized to select data sources relevant to the study’s objectives. Primary data, the original texts and their translations, were sourced from the StoryWeaver website and the Penjaring website respectively. Informants, including raters and children of various ages, assessed translation quality. The study followed four analytical stages: domain analysis, taxonomy analysis, componential analysis, and cultural-theme analysis. Results indicate that the translation attempts to maintain the three aspects. However, while translations emphasize accuracy and acceptability, readability is often compromised due to complex sentence structures and unfamiliar vocabulary. Although readability scores are generally high, young readers frequently struggle with comprehension. This underscores the need to achieve a better balance between fidelity to the source text and accessibility for young audiences.